Application of Chemical Principles in the Preparation of Infused Water as an Educational Effort to Prevent Hyperglycemia at SMK Negeri Pantai Labu - Ritonga, Ahmad Hafizullah; Herlina, Herlina; Harahap, Fitri Ramadani; Sitorus, Rotua Sumihar; Harefa, Karnirius (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Hyperglycemia is characterized by elevated blood glucose levels that can trigger chronic diseases such as diabetes mellitus. Early prevention through science-based education is essential, particularly for adolescents who are vulnerable to unhealthy lifestyles and metabolic disorders. This community service activity aimed to introduce basic chemistry principles through the preparation of infused water as a preventive effort against hyperglycemia and to promote the habit of consuming healthy beverages that can be easily adopted in daily life. The methods used included interactive counseling, demonstrations, and hands-on practice with an applied and participatory approach. The educational content covered concepts such as diffusion, solutes, and solvents, and the extraction process of active compounds from natural ingredients like lemon, cucumber, cinnamon, and mint leaves, which are readily available in the local environment. Evaluation was carried out through pre-tests and post-tests, and observation of participants' engagement during the activity. The results showed a significant increase in participants' understanding, with an average post-test score of 85.2, rising by 32.3 points (61.1%) from the pre-test average of 52.9. A total of 92.86% of participants showed improvement, highlighting the effectiveness of this educational approach. Such initiatives are expected to be continued sustainably and collaboratively to expand their positive impact.